Design and Development of an Electric Gokart Prototype ‘E-Andalasian’ for Sustainable Campus Transportation - Saputra, Dendi Adi; Dahlan, Hendery; Satria, Eka; Susanti, Lusi; Khairul, Fajri; Nabil, M. Naufalunn; Gusnanda, Raihan; Joice Natalie, Ezra; Fadhillah, M. Ahlan (LPPM Universitas Andalas, 2025)
This research focuses on the design, development, and optimization of the electric go-kart